Pelatihan Penyusunan E-Asesmen Literasi Sains Berbasis AKM Bagi Guru IPA SMP di Kabupaten Bogor - Indarini Dwi Pursitasari; Anna Permanasari; Dadang Jaenudin (Jurnal Pemberdayaan Masyarakat, 2022)
Literacy skills for science teachers are needed to be skilled in facilitating the development of students' literacy. The empowerment activity carried out is aimed at improving the ability of science teachers of junior high schools in Bogor Regency in compiling a science literacy e-assessment based on Minimum Competence Assessment (AKM). The participants are teachers who are members of MGMP (Musyawarah Guru Mata Pelajaran) in Bogor Regency. The activity is carried out in the form of Guidance Technique for 4 days followed by an independent task. Teachers' ability or understanding of assessment and scientific literacy is conducted through pretest and posttest. In the end of activity, participants provide an assessment on the implementation of technical guidance that has been organized. The results of the activity show that there is an increase in the teachers' understanding of assessment and scientific literacy with an N-gain achievement of 61.1% and the teachers give a very good assessment both in terms of organizing activities for the preparation of a science literacy e-assessment based on Minimum Competence Assessment (AKM). The conclusion from this empowerment activity is that the training of the preparation of scientific literacy e-assessments has been able to improve teachers' skills in developing a science-based assessment tool.